Strategic elements in the Fort Cooper Coal Measures: potential rare earth elements and other multi-product targets. Issue 3 (2nd April 2020) - Hodgkinson, J. H.; Grigorescu, M.
Abstract: Mineral matter in coals has been found to host valuable elements including germanium, lithium and rare-earth elements (REE), but such content of Australian coals remains under-explored. The aim of this paper is to provide a proof-of-concept study that determines elemental concentrations in the mineral matter of the high-ash, Fort Cooper Coal Measures (FCCM), Bowen Basin, Queensland. Coal in the FCCM has good coking properties but has not been extensively explored owing to its high ash content. This study performs a preliminary assessment of the elements from the coal portion that would typically become waste after washing or combustion. Given that the needs for industrial extraction methods will change over time, cataloguing and documenting the elemental composition of coal may assist future development of multiple products for the benefit of both the coal and mineral industries. This preliminary study has revealed similar elevations of REE and higher-than-average crustal concentrations of lithium, bismuth and scandium in some of the samples. Further analyses will be required on a larger dataset to better understand elemental associations and explore spatial patterns of elemental content that may indicate localised enrichments. Understanding the potential of valuable elements in the FCCM may stimulate interest in multiple-product-coal (or elemental-coal) mining in this under-exploited resource and further encourage the reduction of waste from other Australian coals at the wash-plant stage.